A historical investigation of landscape transformation in the 'Black Swamp' region of northwestern Ohio - Heide, Joni (1995)
The Preservation movement was born out of the realization that a significant portion of our natural and cultural resources are rapidly being consumed, lost, or destroyed in the process of contemporary development. When the preservation movement began, preservationists split into two distinctly separate philosophical groups, Natural Resource Preservationists and Cultural Resource Preservationists. Natural Resource Preservationists focused upon an ecological understanding of the universe, and fought to maintain an ecological balance, while Cultural Resource Preservationists concentrated on saving each archeological or architectural artifact. The result of this divided approach produced monuments to the grand and fantastic, and museums to the famous and nationalistic, but failed to recognize the significance of the `ordinary landscape'. Ordinary landscapes are identified by the material components created by various cultures, and these components are physical representations of the human response to the natural environment that speaks will, beliefs, and the manipulation of the natural world that surrounds them.Recognizing the dynamic and continuously evolving layers of the Cultural Landscape is a critical aspect in Cultural Landscape identification and requires that the symbiotic relationship between the human occupants and the natural environment be understood within the social, political, and natural context. The basis of this project is to establish the social, political and natural context of the Black Swamp region in northwest Ohio in order to reveal the process of landscape transformation in the 'Black Swamp', and to identify areas of the landscape that may contain significant Cultural Landscapes.The 'Black Swamp' lies parallel to the east bank of the Maumee River from Lake Erie southwest to New Haven, Indiana and measures approximately 1500 square miles. Formation of the Black Swamp and the Maumee River Valley began approximately 25,000 years ago, when the Wisconsin glacier advanced southeast out of Canada ...